I24 Quality of life of cypriot patients suffering with huntington's disease. (13th September 2016) - Christou, Yiolanda; Demetriou, Christiana A; Varda, Eleni; Heraclides, Alexandros; Zamba-Papanicolaou, Eleni
Abstract : Background and aim: Despite the enormous burden of Huntington's disease (HD) on the quality of life (QoL) of patients, there is limited evidence on this topic. Given the high prevalence of the disease in Cyprus, the aim of this cross-sectional study was to assess QoL among Cypriot HD patients. Methods: The Euro EQ-5D-3L questionnaire was used. Measures were taken to allow participation of patients at advanced stages and patients unable to visit the clinic. Thirty-four patients were interviewed (46% of the Cypriot HD patient population). Results: Ability of patients to care for themselves and to carry out usual activities were reported to be most severely affected (41.2% and 44.1% replying "Severe Problems" respectively). Mobility and psychosocial well-being were also affected but to a lesser extent (42.5% and 14.7% replying "Severe Problems"). Interestingly, in the anxiety/depression scale, 77.8% of asymptomatic patients reported "Some Problems". Half of the patients did not experience pain or discomfort but 44.1% reported "Some Problems". In multivariate ordinal regression analyses, age at onset and disease duration significantly impacted on mobility and self-care. Number of repeat alleles was a third determining factor on the ability to self-care and disease duration was the only significant determinant of ability to perform usual activities. No significant determinants were evidenced for Pain/Discomfort and Anxiety/Depression (Table 1). Conclusions: Age at onset and disease duration were found to severely affect the QoL of Cypriot HD patients, and more specifically their mobility, ability to self-care and perform usual activities. The percentage of patients reporting "Some Problems" in the Pain/Discomfort category can be explained by the direct translation of the word as presented in the questionnaire, indicating the need for language specific instruments. Perhaps more noteworthy is the phychosocial burden on even asymptomatic patients, which needs to be acknowledged and managed to improve their quality of life.